Agent Banking, Mobile Money Operation and Financial Inclusion in Nigeria: Supply Side Perspective - Quadri, Yusuf Olamilekan; Ayorinde Olutimi Akinwumi; Kudirat Mopelola Malik-Abdulmajeed; Ifedolapo Oluwasolape Omotosho (TIJAB (The International Journal of Applied Business), 2024)
Background: The inability to achieve optimum financial inclusion in Nigeria has necessitated the review of various policies and instruments meant to reduce the level of financial exclusion. Objective: Hence this study investigates the impact of agent banking and mobile money operation on financial inclusion in Nigeria, focusing on the supply side. Method: Descriptive research design was adopted and secondary data ranging from 2013 to 2021 were obtained from the World Bank Global Financial database and e-payment statistics of the Central Bank of Nigeria. Ordinary least squares repression was used to analyse the data. Results: Findings revealed that at 5% significance level, point-of-sale and mobile money operations have a positive impact on financial inclusion while web/internet banking plays a limited role in achieving financial inclusion. Conclusion: The study concluded that both agent banking and mobile money operations impact on financial inclusion in Nigeria; the study, therefore, recommends that more off-site automated teller machine and licensed agents should be encouraged to cater for the rural residents and ultimately improve financial inclusion. Keywords: Agent Banking, Financial inclusion, Mobile Money Operation